Un coeur en hiver - Ravel, Maurice 1875-1937; Sarde, Philippe 1945- (Studio Canal, 2011)
Stéphane and Maxime run a renowned violin making and repair business. One day Maxime introduces his partner to Camille, the beautiful violinist he has been seeing. Camille is attracted to the enigmatic, introverted Stéphane who it seems may share her feelings but is incapable of expressing emotion. Convinced that she can find love beyond his cold exterior, her attraction turns to obsession and culminates in a shattering climax